If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(d-13)=-8
We move all terms to the left:
-2(d-13)-(-8)=0
We add all the numbers together, and all the variables
-2(d-13)+8=0
We multiply parentheses
-2d+26+8=0
We add all the numbers together, and all the variables
-2d+34=0
We move all terms containing d to the left, all other terms to the right
-2d=-34
d=-34/-2
d=+17
| -1=-0.5(b+2)+3b | | -1/n-93=-7 | | -67-j/5=74 | | 75+f/8=83 | | 2(q-10)=18 | | c+7/5=5 | | 29+p/10=36 | | -2(s-98)=10 | | m+18/7=4 | | m+18/17=4 | | -3(m+15)=-15 | | -4(1.5x-5)+4x=2 | | 4=-4w+2(w-7) | | 15x-6=10x+6 | | 2(3x+2)+1=29 | | 6u-62=4u | | 3y+54=12y | | 18=3/4(36.4-n | | 63=15w-8w | | 21+2f=23 | | 5.31=p9. | | (2x-8)(2x-4)=0 | | 1/3y+8=4 | | 3.4(-3x-11)=-49.3(3x-16) | | 2x+100=70 | | 6m+1.25=6.9 | | -2x+24=4x+6 | | -20=m/14 | | y=22/11 | | 6-4(x+1)=2(3x+2) | | x+2x+x+2x=12 | | (18-x)60=(x-3)40 |